Phosphorylation at Y1065 in Vinculin Mediates Actin Bundling, Cell Spreading, and Mechanical Responses to Force - Tolbert, Caitlin E. (American Chemical Society, 2014)
[Image: see text] Vinculin is an essential structural adaptor protein that localizes to sites of adhesion and is involved in a number of cell processes including adhesion, spreading, motility, force transduction, and cell survival. The C-terminal vinculin tail domain (Vt) contains the necessary structural components to bind and cross-link actin filaments. Actin binding to Vt induces a conformational change that promotes dimerization through the C-terminal hairpin of Vt and enables actin filament cross-linking. Here we show that Src phosphorylation of Y1065 within the C-terminal hairpin regulates Vt-mediated actin bundling and provide a detailed characterization of Y1065 mutations. Furthermore, we show that phosphorylation at Y1065 plays a role in cell spreading and the response to the application of mechanical force.